Anchorable Perylene Diimides as Chemically Inert Electron Transport Layer for Efficient and Stable Perovskite Solar Cells with High Reproducibility. Issue 3 (25th January 2021) - Ye, Fangyuan; Zhang, Diwei; Xu, Xiaojia; Guo, Huanxin; Liu, Shuaijun; Zhang, Shuo; Wu, Yongzhen; Zhu, Wei-Hong
Abstract : Oxide semiconductors like TiO2 and SnO2 are exclusively used to construct electron transport layer (ETL) in n–i–p‐structured perovskite solar cells (PSCs). Despite high electron mobility and suitable energy levels, their complicated surface chemistry is detrimental to the interfacial stability as well as fabrication reproducibility. Alternatively, organic n‐type semiconductors address these issues due to their defined molecular structures. Herein, the novel use of anchorable perylene diimides (PDI) and naphthalene diimide (NDI) as chemically inert ETLs is proposed to improve the stability and reproducibility of n–i–p‐structured PSCs. Compared with NDI, the PDI analogues show more suitable lowest unoccupied molecular orbital (LUMO) energy levels (−4.1 vs. −3.8 eV) for matching the conduction band edge of metal halide perovskites, thus favoring the interfacial electron collection. The anchoring chains decorated on PDI entity are found to affect not only the solution processability of ETLs, but also the crystal quality of perovskites. More importantly, the interfacial perovskite decomposition is suppressed in such organic ETLs‐based PSCs. These merits of the anchorable PDI‐based ETLs enable ≈19% efficiency devices with excellent reproducibility and long‐term stability, which outperform traditional TiO2 ‐based n–i–p PSCs. Abstract : A series of anchorable perylene diimide derivatives are explored to construct efficient and chemically inert electron transport layers (ETLs) for n–i–p‐structured perovskite solar cells. The ETLs effective electron extraction, high solvent resistance, improved perovskite crystallization, and suppressed interfacial perovskite decomposition, achieving ≈19% devices efficiency with high reproducibility and excellent stability.